Dynamics Simulation Analysis of Gear Transmission System Under the Impact Load - Lü Kaibo; Hu Xiaohe; Chang Zongxu; Chang Hao; Lian Zisheng (Jixie chuandong, 2016)
The impact load is the main reason that reduces the useful life of the gear transmission system.At first,the 3D virtual prototype of controlled start transmission（ CST） gearbox transmission part is created by Pro / E and then imported into ADAMS. The dynamics simulation of the gear system under impact load is carried out. The meshing force and various transmission angular velocities and frequency spectrum curve are solved,and the variation situation of the mesh force and its frequency-domain characteristic under the impact load or no impact load are compared,the result shows that the gear mesh frequency vibration energy increases obviously because of the impact load. The simulation results is closed to the theoretical analysis result. This study could provide data to be used for the subsequent calculation of gear fatigue life with considering the impact load.